Profile of hospital care for external causes in public hospitals - Marlos Victor Fonsêca de Lima; Romântiezer Lourenço Pereira Silva; Nicelha Maria Guedes de Albuquerque; Jonas Sâmi Albuquerque de Oliveira; Cleonice Andréa Alves Cavalcante; Maria Lúcia Azevedo Ferreira de Macêdo (Universidade Federal do Ceará, 2012)
This study aimed to identify the profile of external causes in the emergency room of a public reference hospital in the state. Descriptive research document with a quantitative approach. The data analysis revealed that from January to December 2009 were made 4464 external causes. The higher frequency of injuries occurred in individuals aged 21 to 40 years (37.70%), males (68.6%). Regarding the causes, falls (29%) was the biggest variable, followed by motorcycle accidents (17.98%), domestic accidents (16.53%), physical abuse (10.43%) and bicycle accident (8, 84%). It was observed that 23.3% of the visits made to the emergency room were the people coming from surrounding municipalities. The study revealed the need to improve the quality of information about the grievances motivated by external causes, which are major causes of hospitalization and health care expenses.